The physiology of deep-water running - Reilly, T.; Dowzer, C. N.; Cable, N. T. (Journal of Sports Sciences, 2003)
Deep-water running is performed in the deep end of a swimming pool, normally with the aid of a flotation vest. The method is used for purposes of preventing injury and promoting recovery from strenuous exercise and as a form of supplementary training for cardiovascular fitness. Both stroke volume and cardiac output increase during water immersion: an increase in blood volume largely offsets the cardiac decelerating reflex at rest. At submaximal exercise intensities, blood lactate responses to exercise during deep-water running are elevated in comparison to treadmill running at a given oxygen uptake (VO2). While VO2, minute ventilation and heart rate are decreased under maximal exercise conditions in the water, deep-water running nevertheless can be justified as providing an adequate stimulus for cardiovascular training. Responses to training programmes have confirmed the efficacy of deep-water running, although positive responses are most evident when measured in a water-based test. Aerobic performance is maintained with deep-water running for up to 6 weeks in trained endurance athletes; sedentary individuals benefit more than athletes in improving maximal oxygen uptake. There is some limited evidence of improvement in anaerobic measures and in upper body strength in individuals engaging in deep-water running. A reduction in spinal loading constitutes a role for deep-water running in the prevention of injury, while an alleviation of muscle soreness confirms its value in recovery training. Further research into the applications of deep-water running to exercise therapy and athletes' training is recommended.